(untitled) (Medical Forum Monthly, 2024)
Objective: To see the clinical presentation of Stroke and risk factors Study Design: Descriptive / Cross Sectional Study Place and Duration of Study: This Study was conducted in the department of Medicine at PMCH Nawabshah from November 2015 to February 2017. Materials and Methods: 115 patients were enrolled for this study 67 were males and 53 were females, informed consent was taken from all the relatives of patients using Questionnaire translated into local languages,statical analysis was done using SPSS 15 version. Results: Age range from 47 to76 years mean age was 63.91-+8.05. 38 patients were drowsy or unconscious. Out of 115 patients 70 patients were diagnosed as Ischemic Stroke and 45 as Hemorrhagic Stroke diagnosed using CT Scan Brain. 84 patients were diabetic, 95 patients were hypertensive and 31 patients were non diabetic and 20 patients were non hypertensive, cholesterol level ranged 153-294 mgwas , RBS ranged 120-452 mg. 96 patients were discharged and19 patients expired due to severity of disease and complications. Conclusion: Stroke is a major problem in our country, main risk factor noted was diabetes, hypertension, hyperlipidemia and old age. Proper treatment of diabetes, hyperlipidemia , hypertension and counseling about disease mortality and mobidity can be reduced.